Preliminary project design for insect production: part 1 – overall mass and energy/heat balances - Kok, R (Journal of insects as food and feed, 2021)
Preliminary project design (PPD) is an initial stage in project development that makes it possible for an entopreneur to gain insight into the feasibility and potential profitability of setting up an insect production facility. In this paper a simple, spreadsheet-based model is presented to facilitate the first step of PPD by estimating the overall mass and energy balances for a proposed project. The model calculates outputs on the basis of scientific data and estimated values for operating parameters for the system that is proposed. With the model it is easy to use a trial-and-error approach to investigate the effect of different parameter values on system operation. Thus, the entopreneur can enter values for parameters such as feed composition, temperature of the cooling air, etc. and see the effect on system productivity, conversion efficiency, energy requirements, etc. immediately. This facilitates the overall procedure of reaching final decisions about the organism, the feed, the processing approach, the scale of operation, etc. Normally, this is an iterative procedure that is based on ‘trial-and-error’, the two aspects being referred to here as the ‘twin components of an iterative knowledge engine’. Thus, the outputs from the model will depend very much on the scientific data supplied and the values of the input parameters while, at the same time, use of the model will highlight what additional scientific data is needed and what alternate parameter values might prove profitable. Overall, the model allows the user to explore a large possibility space for both process constitution and operation much more quickly and easily than by experimental means alone. As such, it is a tool that can aid the entopreneur in thinking about a project and considering various alternatives, as well as in making decisions before a major commitment is made to any particular option. It is stressed here that PPD is only a preliminary stage in project development and that the investigation of overall process mass and energy balances is only the first step thereof. It is also stressed that results from modelling are invariably subject to empirical verification as well as ‘common-sense filtering’. The model presented is general and thus not oriented to the production of any species in particular.